Phytochemical Composition and Anti‐Aging Activity of Butanol Extract of Hedyotis diffusa in Caenorhabditis elegans. Issue 2 (13th January 2022) - Li, Jing; Liu, Di; Li, Danqing; Guo, Yujie; Du, Hongzhi; Cao, Yan
Abstract: Hedyotis diffusa Willd. ( H. diffusa ), a kind of traditional Chinese medicine, has been evaluated to potential display antioxidant and anti‐aging effects in vitro experiments. In this work, we investigated the effects on lifespan and stress resistance of the butanol extract from H. diffusa (NHD) in vivo using a Caenorhabditis elegans ( C. elegans ) model. The phytochemicals of NHD were identified by UPLC‐ESI‐qTOF‐MS/MS method. NHD‐treated wild‐type N2 worms showed an increase in survival time under both normal and stress conditions. Meanwhile, NHD promoted the healthspan of nematodes by stimulating growth and development, reducing the deposition of age pigment, increasing the activities of superoxide dismutase (SOD) and glutathione peroxidase dismutase (GSH‐Px), and decreasing the level of ROS without impairing fertility. Moreover, the upregulating of the expression of daf‐16, gst‐4, sod‐3, hsp12.6 genes and the downregulating of the expression of daf‐2 were involved in the NHD‐mediated lifespan extension. Finally, the increasing of the expression of GST‐4::GFP in CL2166 transgenic nematodes and the life‐span‐extending activity of NHD was completely abolished in daf‐2 and daf‐16 mutants further revealed that the potential roles for these genes in NHD‐induced longevity in C. elegans . Collectively, our findings suggest that NHD may have an active effect in healthy aging and age‐related diseases. Abstract :